An Assessment Of Task Based Instruction In The Efl Classroom: Gacheno Secondary And Preparatory School In Focus. - Habtie Gebremariam (My University, 2016)
The research is written with the intention of assessing teachers’ challenges in implementing task based language teaching instructions in English language classroom. The study was conducted at Gachano secondary and Preparatory school which is found in SNNPRS at Damat Gale Woreda. The participants of the study were grade ten teachers and students in the year 2016 G.C. Purposive sampling techniques were used for teachers’ questionnaire and interview and proportional stratified sampling was used for students interview based on their grade nine results. To conduct the study both qualitative and quantitative research design was used. To gather valid and reliable data, questionnaire, interview, observation and data analysis were used as data gathering tools. The questionnaire was collected from eight English language teachers. Similarly eight teachers and fourty students were participated to get data from interview. On the other hand, four sections were selected from the total of ten for actual classroom observations and they were observed for three consecutive periods each. The data collected from textbook analysis was collected through standardized evaluation checklist adopted from scholars. The data collected from teachers’ questionnaire was analyzed by using percentage and frequency. However, the data gathered from interview, observation and document analysis were analyzed qualitatively in words. The finding of the data collected from all tools revealed that almost all English language teachers in the study area do not have clear understanding about the concept of TBLTI. In spite of this, they have limited involvement in implementing it rather they still depends on traditional language teaching method in a more controlled ways. Moreover, among many challenges that minimize teachers’ active involvement to implement TBLTI were lack of training and awareness about the approach, students interest to learn cooperatively, large class size, traditional teaching habits and unclear instructions and activities in the textbook were found the major finding among the many others were hindrances that minimize their dedication to implement it. Generally, appropriate conclusions and recommendations were forwarded.
Gacheno Secondary And Preparatory School In Focus.